Influence of Profit Sharing Funds and Regional Financial Performance in the Previous Year on the Allocation of Capital Expenditures in Provincial Governments in Indonesia in 2016 – 2020 - Choms Gary Ganda Tua Sibarani; Jihen Ginting; Vivi Afriliani; Nasrullah Hidayat (CERED Indonesia Institute, 2022)
This research is aimed at testing the influence of revenue sharing funds, the previous year's ratio of local independence, the previous year's effectiveness, the previous year's expenditure harmony toward capital expenditure allocation in the provincial government in Indonesia in 2016-2020. The data used in this research is secondary data which is obtained from access to financial reports from the website www.djpk.depkeu.go.id. Analysis of the data in this research using a quantitative approach with statistical descriptive tests, classic assumption tests, multiple regression analysis and hypothesis testing was helped by SPSS 22. The results of this research indicate that the revenue sharing fund variable has no effect on capital expenditure with a significant value of 0.055> 0.05. An independent variable independence ratio from the previous year affects capital expenditure allocation in a negative direction with a significant value of 0.017<0.05. The higher the independence ratio, the lower the capital expenditure allocation. The previous year's effectiveness variable did not affect the allocation of capital expenditure with a significant value of 0.224> 0.05. An independent variable expenditure harmony ratio from previous year affects capital expenditure allocation in a negative direction with a significant value of 0.000<0.05. And simultaneously revenue sharing fund, financial independence of the previous year, the effectiveness of the previous year.